Gender identity and nonbinary pronoun use: exploring reference strategies for referents of unknown gender - Sheydaei, Iman (Gender and Language, 2021)
This study contributes to the emerging literature on gender identity and pronoun use by exploring strategies to refer to unknown human referents. In an online survey involving mainly a university population aged 29 and below, participants were first asked to pick a potential roommate from two fictional characters with gender-ambiguous names and write short answers explaining their choice. Secondly, participants were explicitly asked what pronoun they would use to refer to an unknown human referent from a list of neopronouns in addition to singular they. The results show a strong association between participants’ self-identified gender and the gendered pronoun used. The results also show singular they is the most popular gender-inclusive pronoun for an unknown individual while pronoun avoidance strategies include repeating names and using generic nouns. Additionally, the reflexive form themself is preferred over themselves for unknown human referents, in contrast to previous research showing almost the same rate of naturalness for themselves and themself in the specific-reference context.